Malignant pleural effusion: Updates in diagnosis, management and current challenges - Addala, Dinesh Narayan; Kanellakis, Nikolaos I.; Bedawi, Eihab O.; Dong, Tao; Rahman, Najib M. (Frontiers in Oncology, 2022)
Malignant pleural effusion (MPE) is a common condition which often causes significant symptoms to patients and costs to healthcare providers. Over the past decade, the management of MPE has progressed enormously with large scale, randomised trials answering key questions regarding optimal diagnostic strategies and effective management strategies. Despite a number of management options, including talc pleurodesis, indwelling pleural catheters and combinations of the two, treatment for MPE remains palliative and symptom directed. The future goals for providing improved care for patients lies in changing the treatment paradigm from a generic pathway to personalised care, based on probability of malignancy type and survival. This article reviews the current evidence base, new discoveries and future directions in the diagnosis and management of MPE.